Peluang Evangelisasi di Media Sosial: Kajian Keterlibatan Pelajar Katolik di Yogyakarta - Yohanes Subali; Edyson Hermanto; Marcelinus Wahyu Setyo Aji (Jurnal Teologi (Journal of Theology), 2025)
The development of technology and social media offers a significant opportunity for evangelization. Social media facilitates the formation of digital communities that support faith growth and spiritual involvement. This study examines the engagement of Catholic students in Yogyakarta in using social media as a means of mission. The hypothesis of this research is: Catholic students in Yogyakarta understand mission in a broader context, not only as a physical assignment but also as the dissemination of religious messages through digital platforms. The method used is a qualitative approach involving a literature review and a survey using Google Forms distributed to 120 Catholic students at the high school and university levels in Yogyakarta. This research aims to analyze the level of involvement of Catholic students in using social media for missionary activities. The results of this study are divided into three stages: (1) an explanation of the concept of mission and its development within the Catholic Church, (2) the Catholic Church's response to social media as a major opportunity for mission in the digital age, and (3) the presentation of research findings regarding Catholic students' perspectives on mission on social media. The findings indicate that social media is an effective tool for Catholic students in Yogyakarta to spread religious messages and encourage participation in the Church's missionary activities. This research contributes to the understanding of the role of social media in the Church's mission and offers practical insights for religious communities in the digital era.AbstrakPerkembangan teknologi dan media sosial menawarkan peluang besar untuk evangelisasi. Media sosial memfasilitasi pembentukan komunitas digital yang mendukung pertumbuhan iman dan keterlibatan spiritual. Penelitian ini mengkaji keterlibatan pelajar Katolik di Yogyakarta dalam menggunakan media sosial sebagai sarana misi. Hipotesis penelitian ini adalah: pelajar Katolik di Yogyakarta memahami misi dalam konteks yang lebih luas, tidak hanya sebagai perutusan fisik tetapi juga sebagai penyebaran pesan-pesan keagamaan melalui platform digital. Metode yang digunakan adalah metode kualitatif dengan pendekatan studi pustaka dan survei menggunakan Google Forms kepada 120 pelajar Katolik di tingkat SMA dan perguruan tinggi di Yogyakarta. Penelitian ini bertujuan untuk menganalisis tingkat keterlibatan pelajar Katolik dalam menggunakan media sosial untuk kegiatan misi. Hasil penelitian ini terbagi dalam tiga tahap: (1) penjelasan tentang konsep misi dan perkembangannya dalam Gereja Katolik, (2) tanggapan Gereja Katolik terhadap media sosial sebagai peluang besar dalam misi di era digital, dan (3) pemaparan hasil penelitian mengenai pandangan pelajar Katolik terhadap misi di media sosial. Temuan menunjukkan bahwa media sosial merupakan alat efektif bagi pelajar Katolik di Yogyakarta untuk menyebarkan pesan keagamaan dan mendorong partisipasi dalam kegiatan misi Gereja. Penelitian ini memberikan kontribusi terhadap pemahaman peran media sosial dalam misi Gereja dan menawarkan wawasan praktis bagi komunitas religius di era digital.